2018
DOI: 10.3390/catal8110539
|View full text |Cite
|
Sign up to set email alerts
|

MPV Reduction of Furfural to Furfuryl Alcohol on Mg, Zr, Ti, Zr–Ti, and Mg–Ti Solids: Influence of Acid–Base Properties

Abstract: The Meerwein–Ponndorf–Verley (MPV) reaction is an environmentally-friendly process consisting of the reduction of a carbonyl compound through hydrogen transfer from a secondary alcohol. This work deals with MPV reduction of furfural to furfuryl alcohol on different ZrOx, MgOx, TiOx, and Mg–Ti, as well as Zr–Ti mixed systems. The solids were synthesized through the sol–gel process and subsequently calcined at 200 °C. Characterization was performed using a wide range of techniques: ICP-MS, N2 adsorption-desorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…For example, Urbano and coworkers employed various transition metal oxide catalysts, including ZrO x , MgO x , and TiO x , for the transfer hydrogenation of FUR at 100°C using 2-propoanol as H-donor solvent. [28] Among these catalysts, ZrO x afforded maximum FUR conversion (50 %) and the highest FOL selectivity (90 %). Characterization of these catalysts revealed that ZrO x possessed both Lewis acidic and Lewis basic sites, and the basic to acidic site ratio obtained from CO 2 TPD and pyridine TPD was 1.1.…”
Section: Transfer Hydrogenation Of Fur To Fol Using Alcohol As H-donorsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Urbano and coworkers employed various transition metal oxide catalysts, including ZrO x , MgO x , and TiO x , for the transfer hydrogenation of FUR at 100°C using 2-propoanol as H-donor solvent. [28] Among these catalysts, ZrO x afforded maximum FUR conversion (50 %) and the highest FOL selectivity (90 %). Characterization of these catalysts revealed that ZrO x possessed both Lewis acidic and Lewis basic sites, and the basic to acidic site ratio obtained from CO 2 TPD and pyridine TPD was 1.1.…”
Section: Transfer Hydrogenation Of Fur To Fol Using Alcohol As H-donorsmentioning
confidence: 99%
“…Several research groups have employed transition metal oxide catalysts, and the activity of these catalysts has been attributed to both Lewis acid and Lewis basic sites, which facilitate the hydrogen transfer from the H‐donor molecule to FUR and result in FOL production. For example, Urbano and coworkers employed various transition metal oxide catalysts, including ZrO x , MgO x , and TiO x , for the transfer hydrogenation of FUR at 100 °C using 2‐propoanol as H‐donor solvent [28] . Among these catalysts, ZrO x afforded maximum FUR conversion (50 %) and the highest FOL selectivity (90 %).…”
Section: Furfuryl Alcohol (Fol)mentioning
confidence: 99%
See 2 more Smart Citations
“…A number of heterogeneous catalysts have been developed for the MPV reduction, [19] such as, zeolites, [20][21][22][23][24][25] mesoporous silicates, [26] hydrotalcite, [27,28] metal oxides [29][30][31][32][33][34][35] or metal-organic frameworks. [36,37] However, most of them involve complex synthetic routes with the incorporation of various metals [24,25,38,39] and in some cases rare metals.…”
Section: Introductionmentioning
confidence: 99%